COVID-19 and social work in health care in Canada: What are the impacts?. (21st April 2022) - Cadell, Susan; Ashcroft, Rachelle; Furtado, Jessica; Adamson, Keith; McConnell, Sheri M; Teichman, Samantha
ABSTRACT: The COVID-19 pandemic has profoundly affected the world. In Canada, the impact has been worrisome. Canada is a large, sparsely populated country with a system of universal health care that is decided nationally and enacted by each province and territory. There are variations in health care, as well as in the provision of social work, throughout the country. The aim of this survey is to examine the impact of the COVID-19 pandemic on social workers employed in health care. Participants were recruited for an online survey via social media, professional associations, and social work education programs. Three hundred and seventy-six social workers participated. Analyses were performed to: (1) investigate the changes in workplace conditions indicated by social workers as a result of the COVID-19 pandemic; (2) examine reported levels of distress, social support, quality of professional life, resilience, and posttraumatic growth among respondents during this time; and (3) contextualize these findings by exploring similarities and differences across geographic locations. Many respondents were deemed essential workers. Significant differences across regions were not found. The knowledge generated has important implications for all sectors of the social work profession in Canada.